1999
DOI: 10.1088/0031-9155/44/10/301
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of change in brain temperatures due to exposure to a mobile phone

Abstract: In this study we evaluated for a realistic head model the 3D temperature rise induced by a mobile phone. This was done numerically with the consecutive use of an FDTD model to predict the absorbed electromagnetic power distribution, and a thermal model describing bioheat transfer both by conduction and by blood flow. We calculated a maximum rise in brain temperature of 0.11 degrees C for an antenna with an average emitted power of 0.25 W, the maximum value in common mobile phones, and indefinite exposure. Maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
118
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(133 citation statements)
references
References 26 publications
13
118
0
2
Order By: Relevance
“…This hypothesis has recently been proposed especially for the highest frequencies, in which dielectric and resistive heating could increase the local temperature and increase the entropy of the exposed biologic system (Sheppard et al, 2008). However, a thermal mechanism should be rejected taking into account that: (1) the distance between the antenna and the head drastically reduces the absorbed power (Schö nborn et al, 1999); (2) increase of skin temperature would be easily dissipated through the blood flow (Van Leeuwen et al, 1999); and (3) near-infrared light penetrates through the brain at least 1.5 cm in-depth, in which temperature changes are far below the danger level (Wang and Fujiwara, 1999;Bernardi et al, 2000). Thus, several nonthermal mechanisms could be involved, such as: (1) proteins conformational variations resulting in proteins functional changes; (2) modifications in the binding of ligands, such as Ca + + to cell receptors, also resulting in a changed receptor function; (3) absorption of RF energy by the vibrational states of biologic components, such as microtubules; (4) enhanced attraction amongst cells (the pearl-chain effect); and (5) demodulation of a modulated RF signal, producing extremely lowfrequency electric fields (for a review, see Challis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has recently been proposed especially for the highest frequencies, in which dielectric and resistive heating could increase the local temperature and increase the entropy of the exposed biologic system (Sheppard et al, 2008). However, a thermal mechanism should be rejected taking into account that: (1) the distance between the antenna and the head drastically reduces the absorbed power (Schö nborn et al, 1999); (2) increase of skin temperature would be easily dissipated through the blood flow (Van Leeuwen et al, 1999); and (3) near-infrared light penetrates through the brain at least 1.5 cm in-depth, in which temperature changes are far below the danger level (Wang and Fujiwara, 1999;Bernardi et al, 2000). Thus, several nonthermal mechanisms could be involved, such as: (1) proteins conformational variations resulting in proteins functional changes; (2) modifications in the binding of ligands, such as Ca + + to cell receptors, also resulting in a changed receptor function; (3) absorption of RF energy by the vibrational states of biologic components, such as microtubules; (4) enhanced attraction amongst cells (the pearl-chain effect); and (5) demodulation of a modulated RF signal, producing extremely lowfrequency electric fields (for a review, see Challis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although in this paper applications were focussed on hyperthermia, the software package is more widely applicable for electromagnetic and thermal simulations, for example in research on high field MRI, RF ablation, mobile phones or RF safety in general [100][101][102][103][104][105][106][107]. With the widespread use of MR investigations and the increasing field strength of MR scanners, safety aspects become very important and the risk of MR-induced hot-spots can be evaluated using simulations [106].…”
Section: Discussionmentioning
confidence: 99%
“…Below the exposure limits, however, potentially damaging temperature increases are prevented: while for whole-body exposure, thermal effects are negligible, local exposure (i.e., by using a mobile phone) leads to temperature increases of less than 1uC only in close proximity of the antenna, mainly in the ear pinna, the ear canal, 5 the skin and parts of the brain where the temperature increase due to exposure is on the order of 0.1uC. 6 One of the common misunderstandings by laymen is the warmth perception at the ear pinna after a long telephone call which is believed to be caused by RF-EMF. Studies have clearly shown that RF-EMF is responsible for only a small fraction of this temperature increase, while the major contribution comes from the insulation (i.e., less heat dissipation by the ear pinna) and heating by the phone's battery and electric circuits during operation.…”
Section: Thermal Versus Non-thermal Effectsmentioning
confidence: 99%
“…Studies have clearly shown that RF-EMF is responsible for only a small fraction of this temperature increase, while the major contribution comes from the insulation (i.e., less heat dissipation by the ear pinna) and heating by the phone's battery and electric circuits during operation. 6 'Radiation' The electromagnetic fields emitted by mobile phones and other wireless devices are often called 'radiation' which is at least misleading. Radiation is the commonly used term for ionizing radiation, i.e., high-energy photons (e.g., UV-C, X-rays, c-rays) or particles (a and b), which can ionize atoms and molecules and can therefore lead to mutations and cancer.…”
Section: Thermal Versus Non-thermal Effectsmentioning
confidence: 99%